Calcium chloride as firming agent for pickled onion (Allium cepa var. red creole) - Barit, Phoebe Villanueva (2002.)
A study investigating the effectiveness of CaCl2 as firming agent in pickled onion was conducted in complete randomized design (CRD) experiment.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Calcium chloride; Firming agent; Onion